The nurse's approach in primary health care to women in climateric (Research, Society and Development, 2023)
The present study aims to identify the factors that interfere with the approach of nurses in Primary Health Care, in relation to women in the climacteric. This is a research with a qualitative approach, of the descriptive type, along the lines of a bibliographic review. As the result of crossing the descriptors in Health Sciences (DeCS) and searching the main databases (BVS, BDENF, LILACS, Medline, SciELO), it was possible to extract, after a detailed reading, a selection of 12 studies. In the synthesis, two themes emerged: knowledge and practices of nurses about the climacteric and health education as a care strategy for women in the climacteric. Followed by an integrated discussion of each theme, in order to respond the research objectives, it became evident the shortage of investment of a political and academic nature in the sphere of women's health, in addition to the insufficient knowledge of nurses in managing the climacteric, which culminate in few health actions aimed to the public and a lack of investment in health education.